Anticonvulsant effect of glycitin in pentylenetetrazol induced male Wistar rat model by targeting oxidative stress and Nrf2/HO-1 signaling - Hakimi Naeini, Saghi; Rajabi-Maham, Hassan; Azizi, Vahid; Hosseini, Abdolkarim (Frontiers in Pharmacology, 2024)
Epilepsy, characterized by recurrent seizures, poses a significant health challenge globally. Despite the availability of anti-seizure medications, their adverse effects and inadequate efficacy in controlling seizures propel the exploration of alternative therapeutic measures. In hypothesis, glycitin is a phytoestrogenic compound found in soybeans and due to its estrogenic properties may have anti-epileptic and neuroprotective effects. This study investigates the potential anti-epileptic properties of glycitin in the context of pentylenetetrazol (PTZ) induced seizures in male Wistar rats. The rats were pretreated with varying doses of glycitin (5, 10 and 20 mg/kg) before PTZ (35 mg/kg) administration, and assessments included behavioral observations and histological evaluation via hematoxylin and eosin (H&E) staining. Additionally, oxidative stress markers, such as malondialdehyde (MDA), glutathione peroxidase (GPx), and superoxide dismutase (SOD) levels, were quantified to examine glycitin's impact on oxidative stress. Molecular analysis was conducted to assess the activation of the Nuclear factor erythroid 2-related factor (Nrf2)/Heme oxygenase 1 (HO-1) signaling pathway. Results indicated that glycitin pretreatment effectively mitigated PTZ-induced convulsive behaviors, supported by histological findings from H&E staining. Furthermore, glycitin administration led to significant alterations in MDA, GPx, and SOD levels, suggestive of its ability to modulate oxidative stress. Notably, glycitin treatment induced activation of the Nrf2/HO-1 signaling pathway. These findings underscore the potential of glycitin as an anticonvulsant agent, elucidating its mechanism of action through histological protection, modulation of oxidative stress markers, and activation of the Nrf2/HO-1 signaling pathway.